Vibration damper
Patent Information
- Application Number
- JP2024192074
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2044-10-31
AI Technical Summary
【0010】 本発明によれば、減衰特性に優れる制振ダンパーを提供できる。
Smart Images

Figure 0007630701000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a vibration damper, and more particularly to a vibration damper suitable for applications such as vibration control and seismic isolation in the fields of civil engineering and construction. [Background technology]
[0002] In the fields of civil engineering and construction, vibration control devices and seismic isolation devices, particularly vibration dampers (also called seismic isolation dampers) used in large structures such as bridges and buildings, it is required that the mechanical structural elements of the vibration control damper exert vibration control performance in order to absorb vibration energy caused by earthquakes, etc., and that the viscoelastic material (rubber material) used in the vibration control damper achieve high damping.
[0003] Furthermore, the 2016 Ministry of Land, Infrastructure, Transport and Tourism guidelines included instructions on how to respond to long-period earthquake motion (convergence time of 600 seconds) for high-rise buildings, and this has created a growing need for vibration control dampers whose damping characteristics do not decrease even with shaking that has a long convergence time.
[0004] Viscoelastic bodies used in conventional vibration dampers mainly contain a styrene-isoprene-styrene (SIS) copolymer as a main component (see, for example, Patent Documents 1 and 2). In addition, in order to develop friction damping properties for SIS copolymers, investigations are being conducted into blending them with ethylene-propylene-diene terpolymers or with small particle size fillers such as silica or calcium carbonate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-227521 A [Patent Document 2] JP 2015-183110 A Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, various studies have been conducted in the past focusing on the damping characteristics of vibration dampers. However, the reality is that research into the relationship between the dispersion form of the filler in the viscoelastic material that constitutes the vibration damper and the damping characteristics, in particular the relationship between the dispersion form of calcium carbonate and the damping characteristics, has not yet progressed sufficiently.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a vibration damper having excellent damping characteristics. [Means for solving the problem]
[0008] The present inventors, in the course of examining combinations of polymer components and filler components from the viewpoint of improving the damping characteristics of a viscoelastic body that is a constituent member of a vibration damper, focused on the dispersion form of calcium carbonate in a polymer matrix containing (A) at least one of a styrene-isoprene-styrene (SIS) copolymer and a styrene-butadiene-styrene (SBS) copolymer, and (B) one or more members selected from the group consisting of an ethylene-propylene-diene terpolymer (EPDM), an ethylene-butene-diene terpolymer (EBT), and a butadiene rubber (BR). In the course of intensive research from this perspective, the inventors have found new findings that are different from those in the past regarding the relationship between the dispersion form of calcium carbonate and the damping characteristics. That is, in the past, it was generally believed that in order to improve various characteristics, it was preferable to increase the dispersibility of calcium carbonate in a polymer matrix, that is, to reduce the proportion of aggregates of calcium carbonate particles as much as possible. However, the inventors have newly discovered that in the above-mentioned specific polymer matrix, as the dispersibility of calcium carbonate increases, the damping characteristics may be adversely impaired. As a result of further research based on this new knowledge, the inventors have found that the damping characteristics of a viscoelastic material, which is a constituent material of a vibration damper, can be effectively improved by having a specific dispersion form, i.e., having three or more calcium carbonate particles in a linked state, and controlling the number of aggregates in which three or more calcium carbonate particles are linked, within a specific range.
[0009] That is, the gist of the present invention is the following [1] to [5]. [1] A vibration damper comprising, as a constituent member, a viscoelastic body made of a rubber composition containing the following components (A) to (C), wherein the number of aggregates, each of which is made up of three or more linked calcium carbonate particles, contained in any 1 μm × 1 μm square region of a scanning transmission electron microscope image of the viscoelastic body taken at a magnification of 150,000 times is in the range of 3 to 15. (A) At least one of a styrene-isoprene-styrene copolymer and a styrene-butadiene-styrene copolymer (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber (C) Calcium carbonate [2] The vibration damper according to [1], wherein the number of aggregates each including three or more calcium carbonate particles connected together is in the range of 5 to 9. [3] The vibration damper according to [1] or [2], wherein the content of the calcium carbonate is 15 to 100 parts by mass per 100 parts by mass of the total of the components (A) and (B). [4] The vibration damper according to any one of [1] to [3], wherein the calcium carbonate particles have a cubic shape. [5] The vibration damper according to any one of [1] to [4], wherein the calcium carbonate has an average particle size of 10 to 300 nm. Effect of the Invention
[0010] According to the present invention, a vibration damper having excellent damping characteristics can be provided. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a front view showing an example of a vibration damper. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a vibration damper. [Diagram 3] FIG. 11 is a cross-sectional view showing another example of the vibration damper. [Figure 4] FIG. 2 is a schematic diagram showing an installation state of a vibration damper. [Diagram 5] FIG. 1 is a schematic diagram of an apparatus used to carry out the evaluation methods described in the Examples. [Figure 6] FIG. 2 is a diagram showing a load-strain loop curve in the evaluation method described in the Examples. [Figure 7] FIG. 2 is a scanning transmission electron microscope image of Example 1. [Figure 8] FIG. 2 is a diagram showing an element mapping image of Example 1. [Figure 9] FIG. 2 is a diagram showing an enlarged image (1 μm×1 μm square area) of a scanning transmission electron microscope image of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Next, an embodiment of the present invention will be described in detail, although the present invention is not limited to this embodiment.
[0013] In this specification, "X or / and Y (X and Y are optional)" means at least one of X and Y, and means the following three cases: X only, Y only, and X and Y. In addition, for the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range can be arbitrarily combined with the upper limit or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range can be replaced with the value shown in the examples.
[0014] <Vibration damper> A vibration damper according to one embodiment of the present invention (hereinafter may be referred to as "this vibration damper") is a vibration damper having as its constituent member a viscoelastic body made of a rubber composition (hereinafter may be referred to as "this rubber composition") containing the following components (A) to (C), and is characterized in that the number of aggregates, each of which is made up of three or more linked calcium carbonate particles and is contained in any 1 μm × 1 μm square region of a scanning transmission electron microscope image of the viscoelastic body taken at a magnification of 150,000, is in the range of 3 to 15. (A) At least one of a styrene-isoprene-styrene copolymer and a styrene-butadiene-styrene copolymer (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber (C) Calcium carbonate
[0015] This vibration damper has excellent damping characteristics because the calcium carbonate particles have a different dispersion form than conventional ones in a viscoelastic body made of a rubber composition containing components (A) to (C).
[0016] Specifically, excellent damping characteristics can be obtained by setting the number of aggregates, each of which is made up of three or more calcium carbonate particles connected together, to the range of 3 to 15 in any 1 μm×1 μm square region in a scanning transmission electron microscope image of a viscoelastic body made of a rubber composition containing the (A) to (C) components taken at a magnification of 150,000. If the number of aggregates is outside the above range, it is not possible to obtain the excellent damping characteristics of the present invention. For example, if the aggregates are almost absent, as has been conventionally considered to be preferable, for example, if the aggregates are dispersed until the number of aggregates is less than three, it is not possible to obtain the excellent damping characteristics of the present invention.
[0017] In a preferred embodiment of the vibration damper, from the viewpoint of exhibiting particularly excellent damping characteristics, the number of the aggregates is preferably in the range of 3 to 12, and more preferably in the range of 5 to 9. The number of the aggregates can be appropriately adjusted within the above range, and may be, for example, in the range of 6 to 9.
[0018] The number of calcium carbonate particles forming the aggregate is not particularly limited as long as it is 3 or more, but for example, the number of calcium carbonate particles forming the aggregate is about 3 to 10. In one embodiment of the present invention, the number of aggregates each formed of 3 to 10 calcium carbonate particles is preferably in the range of 3 to 15.
[0019] The reason why the vibration damper provides the above-mentioned excellent effect is not entirely clear, but the inventors presume that, since it is necessary to effectively produce frictional force in order to achieve excellent damping properties, in the present invention, in the polymer matrix containing the (A), (B) and (C) components, friction between aggregates containing three or more calcium carbonate particles is significantly improved, and the interparticle attraction between the calcium carbonate particles constituting the aggregates and the mutual friction between the calcium carbonate particles and a specific polymer component further significantly improve the frictional force, thereby obtaining excellent damping properties. In addition, focusing on the fact that poor dispersion of calcium carbonate and too many aggregates tend to make it difficult to achieve frictional damping, and conversely, if the dispersion is too good, a certain amount of displacement is required to achieve frictional damping, in the present invention, by controlling the number of specific aggregates within a specific range, a frictional damping effect can be achieved synergistically, and therefore excellent damping properties can be obtained.
[0020] The number of aggregates can be determined in a conventional manner by the following method. That is, a microtome is used to prepare a smooth surface of the viscoelastic body, and a 1 μm x 1 μm square area is identified in a scanning transmission electron microscope image taken at 150,000 times magnification. The area is then visually observed, and the number of aggregates consisting of three or more calcium carbonate particles linked together is counted.
[0021] Specifically, for example, the viscoelastic body is first observed with a scanning transmission electron microscope at a magnification of 150,000 times to obtain a scanning transmission electron microscope image. Next, an element mapping image is obtained with an energy dispersive X-ray spectrometer attached to the scanning transmission electron microscope, and calcium carbonate in the microscope image is identified by detecting Ca atoms derived from calcium carbonate. Then, the element mapping image is compared with an enlarged image of the electron microscope image, and the number of aggregates contained in a 1 μm × 1 μm square area in the electron microscope image is visually counted.
[0022] In addition, in this specification, an "aggregate having three or more calcium carbonate particles connected together" observed in a scanning transmission electron microscope image means an aggregate including at least a first calcium carbonate particle, a second calcium carbonate particle in contact with the first calcium carbonate particle, and a third calcium carbonate particle in contact with at least one of the first calcium carbonate particle and the second calcium carbonate particle. Specifically, the aggregate is an aggregate in which the outline of a first calcium carbonate particle and the outline of a second calcium carbonate particle are in contact with each other, and the aggregate includes at least a third calcium carbonate particle in contact with at least one of the first calcium carbonate particle and the second calcium carbonate particle.
[0023] In addition, the term "aggregate of three or more calcium carbonate particles" observed in a scanning transmission electron microscope image implies not only that the calcium carbonate particles are in contact with each other, but also that the interparticle distance is within 20 nm, in consideration of the interparticle attractive force of the calcium carbonate particles. In other words, when the interparticle distance between any calcium carbonate particle and another calcium carbonate particle is within 20 nm, the two can be considered to be in contact with each other due to chemical and physical interparticle attractive forces. Therefore, an aggregate including at least a first calcium carbonate particle, a second calcium carbonate particle having an interparticle distance of 20 nm or less from the first calcium carbonate particle, and a third calcium carbonate particle having an interparticle distance of 20 nm or less from at least one of the first calcium carbonate particle and the second calcium carbonate particle can be considered to be an "aggregate of three or more calcium carbonate particles in contact with each other." More specifically, when the shortest straight-line distance between the outline of any calcium carbonate particle and the outline of another calcium carbonate particle is within 20 nm, more specifically, when the shortest straight-line distance between any point constituting the outline of any calcium carbonate particle and any point constituting the outline of another calcium carbonate particle is within 20 nm, the calcium carbonate particles can be regarded as being in contact with each other, and therefore the particle is regarded as an "aggregate of three or more calcium carbonate particles connected together."
[0024] The vibration damper will be described in detail below.
[0025] In one embodiment of the vibration damper, the rubber composition contains at least the polymer components (A) and (B). The polymer components are preferably a polymer component containing the component (A) as a main component.
[0026] The "main component" of the above polymer component means that component (A) accounts for 50 mass% or more of the total amount (100 mass%) of the above polymer component, and may be 60 mass% or more, 70 mass% or more, 80 mass% or more, or 90 mass% or more.
[0027] Furthermore, in one embodiment of the present vibration damper, from the viewpoint of damping characteristics, it is preferable that the polymer component consists only of component (A) and component (B). However, this is not limited to this. For example, of the total amount (100 mass%) of the polymer component, the content of components (A) and (B) may be 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, etc.
[0028] (A) At least one of styrene-isoprene-styrene (SIS) copolymer and styrene-butadiene-styrene (SBS) copolymer The rubber composition contains at least one of a styrene-isoprene-styrene (SIS) copolymer and a styrene-butadiene-styrene (SBS) copolymer. The styrene-isoprene-styrene (SIS) copolymer and the styrene-butadiene-styrene (SBS) copolymer are styrene-based elastomers, and those conventionally known in the art can be used as appropriate.
[0029] (Styrene-isoprene-styrene (SIS) copolymer) The styrene-isoprene diblock content in the SIS copolymer is not particularly limited, but is preferably 50 to 95% by mass, and more preferably 60 to 90% by mass. With such a diblock content, it is more excellent in obtaining high damping characteristics. The diblock content is a value measured by gel permeation chromatography (GPC).
[0030] The styrene content in the SIS copolymer is not particularly limited, but is preferably 10 to 30 mass %, and more preferably 13 to 25 mass %. The styrene content is a value measured by a nuclear magnetic resonance (NMR) spectrometer.
[0031] The number average molecular weight (Mn) of the SIS copolymer is not particularly limited, but is preferably 100,000 to 200,000, and more preferably 100,000 to 150,000. In other words, such a small molecular weight is preferable from the viewpoint of damping characteristics. The number average molecular weight (Mn) is a value measured according to gel permeation chromatography (GPC).
[0032] Mooney viscosity (ML) of SIS copolymer 1+4 (100° C.) is not particularly limited, but is preferably from 10 to 50, and more preferably from 13 to 40, for example.
[0033] The Mooney viscosity in this specification is measured in accordance with the provisions of JIS K6300-1:2013 using an L-shaped rotor under conditions of a preheating time of 1 minute, a rotor rotation time of 4 minutes, and a test temperature of 100°C.
[0034] (Styrene-butadiene-styrene (SBS) copolymer) The styrene-butadiene diblock content in the SBS copolymer is not particularly limited, but is preferably 50 to 95% by mass, and more preferably 60 to 90% by mass. With such a diblock content, it is more excellent in obtaining high damping characteristics. The diblock content is a value measured by gel permeation chromatography (GPC).
[0035] The styrene content in the SBS copolymer is not particularly limited, but is preferably 10 to 30% by mass, and more preferably 13 to 25% by mass, for example. The styrene content is a value measured by a nuclear magnetic resonance (NMR) spectrometer.
[0036] The number average molecular weight (Mn) of the SBS copolymer is not particularly limited, but is preferably in the range of 100,000 to 200,000, and more preferably in the range of 100,000 to 150,000. In other words, such a small molecular weight is preferable from the viewpoint of damping characteristics. The number average molecular weight (Mn) is a value measured according to gel permeation chromatography (GPC).
[0037] Mooney Viscosity (ML 1+4 (100° C.) is not particularly limited, but is preferably from 10 to 50, and more preferably from 13 to 40, for example.
[0038] The rubber composition may contain other components as polymer components than those mentioned above. For example, styrene-based elastomers such as styrene-butadiene (SB) copolymer, styrene-isoprene (SI) copolymer, styrene-ethylene-butylene (SEB) copolymer, styrene-ethylene-butylene-styrene (SEBS) copolymer, styrene-ethylene-propylene (SEP) copolymer, styrene-ethylene-propylene-styrene (SEPS) copolymer, and hydrogenated copolymers of the above-mentioned copolymers may be mentioned. These may be used alone or in combination of two or more kinds.
[0039] Examples of commercially available products of the component (A) include Quintac 3390, Quintac 3433N, and Quintac 3270 (all manufactured by Zeon Corporation), D1161 (manufactured by Kraton Polymers), and VECTOR 4411 (manufactured by TSRC Corporation).
[0040] (B) One or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber The rubber composition contains at least one rubber selected from the group consisting of an ethylene-propylene-diene terpolymer, an ethylene-butene-diene terpolymer, and a butadiene rubber.
[0041] (Ethylene-propylene-diene monomer terpolymer (EPDM)) Any EPDM known in the art can be used as appropriate. The ethylene content of the EPDM is not particularly limited, but is preferably 5 to 60 mass %, more preferably 10 to 40 mass %, from the viewpoint of damping characteristics.
[0042] The propylene content of EPDM is not particularly limited, but is preferably from 5 to 60 mass %, more preferably from 10 to 40 mass %, from the viewpoint of damping characteristics, for example.
[0043] The diene content of the EPDM is not particularly limited, but from the viewpoint of damping characteristics, it is preferably from 3 to 25 mass %, and more preferably from 5 to 15 mass %.
[0044] The diene (third component) of EPDM is preferably a diene monomer having 5 to 20 carbon atoms, and specific examples thereof include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 2,5-dimethyl-1,5-hexadiene, 1,4-octadiene, 1,4-cyclohexadiene, cyclooctadiene, dicyclopentadiene (DCP), 5-ethylidene-2-norbornene (ENB), 5-butylidene-2-norbornene, 2-methallyl-5-norbornene, and 2-isopropenyl-5-norbornene.
[0045] EPDM Mooney Viscosity (ML 1+4 (100° C.) is not particularly limited, but is preferably, for example, in the range of 30 to 100, and more preferably 35 to 85.
[0046] (Ethylene-butene-diene terpolymer (EBT)) As the EBT, any EBT conventionally known in the art can be used as appropriate. The ethylene content of the EBT is not particularly limited, but is preferably, for example, 55 mass% or less, more preferably 35 to 55 mass%, and further preferably 40 to 53 mass%.
[0047] The butene content in EBT is not particularly limited, but is, for example, preferably 35% by mass or more, more preferably 35 to 55% by mass, and further preferably 38 to 50% by mass.
[0048] The diene content of EBT is not particularly limited, but from the viewpoint of damping characteristics, it is preferably 3 to 25 mass %, and more preferably 5 to 15 mass %.
[0049] The diene (third component) of EBT is preferably a diene monomer having 5 to 20 carbon atoms, and specific examples thereof include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 2,5-dimethyl-1,5-hexadiene, 1,4-octadiene, 1,4-cyclohexadiene, cyclooctadiene, dicyclopentadiene (DCP), 5-ethylidene-2-norbornene (ENB), 5-butylidene-2-norbornene, 2-methallyl-5-norbornene, and 2-isopropenyl-5-norbornene.
[0050] (Butadiene rubber (BR)) The butadiene rubber (BR) used in the rubber composition can be any rubber that is conventionally known in the art. The butadiene rubber (BR) is a rubber obtained by polymerizing butadiene as a raw material monomer, and is obtained by polymerizing butadiene using, for example, a Ziegler catalyst or an alkyl lithium initiator.
[0051] The microstructure of the butadiene rubber (BR) is not particularly limited, but a low cis-BR having a cis-1,4 bond unit content of 50% by mass or less, for example, about 30 to 40% by mass, or a high cis-BR having a cis-1,4 bond unit content of 90% by mass or more can be appropriately used.
[0052] Butadiene rubber (BR) Mooney viscosity (ML 1+4 (100° C.) is not particularly limited, but is, for example, about 30 to 60, 30 to 55, or 30 to 50.
[0053] Examples of commercially available products of the component (B) include EPT K-972 and EPT 4045M (all manufactured by Mitsui Chemicals), EP104E, EP35, EP65, EP33, and EP98 (all manufactured by JSR Corporation).
[0054] The mixing ratio of the components (A) and (B) in the rubber composition is preferably (A):(B)=95:5 to 50:50 by mass, and more preferably (A):(B)=90:10 to 55:45.
[0055] In a preferred embodiment of the rubber composition, a styrene-isoprene-styrene (SIS) copolymer and an ethylene-propylene-diene terpolymer (EPDM) are used in combination. The mass ratio of the styrene-isoprene-styrene (SIS) copolymer to the ethylene-propylene-diene terpolymer (EPDM) is preferably SIS:EPDM=95:5 to 50:50, and more preferably SIS:EPDM=90:10 to 55:45.
[0056] (C) Calcium Carbonate It is important that the rubber composition contains calcium carbonate, among various fillers, in addition to components (A) and (B). As described above, it is important that the calcium carbonate has a specific dispersion form.
[0057] As calcium carbonate, any calcium carbonate conventionally known in the art can be used as appropriate. Although not particularly limited, from the viewpoint of significantly achieving the effects of the present invention, for example, calcium carbonate that has been subjected to a surface treatment such as hydrophobization treatment may be used. Specifically, for example, calcium carbonate treated with stearic acid, calcium carbonate treated with rosin acid, calcium carbonate treated with lignin, calcium carbonate treated with a fatty acid quaternary ammonium salt, etc. may be used.
[0058] The average particle size (average primary particle size) of calcium carbonate used in the rubber composition is, for example, 10 to 300 nm. From the viewpoint of significantly exhibiting the effects of the present invention, the average particle size (average primary particle size) of calcium carbonate is, for example, preferably 30 to 100 nm, more preferably 30 to 70 nm. The average particle size (average primary particle size) can be calculated using a scanning transmission electron microscope.
[0059] The particle shape of the calcium carbonate used in the rubber composition may be, for example, a cubic shape, a spindle shape, a disk shape, a hexagonal plate shape, a spherical shape, etc. Among these, the cubic shape is preferable from the viewpoint of further improving the damping characteristics. The cubic shape may be a regular hexahedron or a cube that is close to a regular hexahedron. Specifically, for example, a hexahedron in which the difference in length between each side is ±8 nm or less may be mentioned.
[0060] The BET specific surface area of calcium carbonate is, but is not limited to, for example, 4.0 to 60 m 2 / g, preferably 10 to 40m 2 / g, more preferably 20 to 35m 2 / g. The BET specific surface area of calcium carbonate can be measured, for example, by degassing a sample at 200° C. for 15 minutes and then using a mixed gas (N2: 70%, He: 30%) as an adsorption gas with a BET specific surface area measuring device (Microdata Corporation, 4232-II).
[0061] The DBP (dioctyl phthalate) oil absorption of calcium carbonate is, but not limited to, for example, 15 to 75 cc / 100 g, preferably 20 to 45 cc / 100 g, and more preferably 20 to 30 cc / 100 g.
[0062] From the viewpoint of easily controlling the number of the aggregates within a suitable range, the content of calcium carbonate is, for example, 15 to 100 parts by mass, preferably 25 to 80 parts by mass, more preferably 35 to 70 parts by mass, and even more preferably 40 to 60 parts by mass, relative to 100 parts by mass of the total of the (A) component and the (B) component.
[0063] Other optional ingredients In addition to the components (A) to (C), the rubber composition may contain fillers such as silica and carbon black, processing aids, antioxidants, crosslinking agents, crosslinking accelerators, etc., as long as they do not impair the effects of the present invention. These may be used alone or in combination of two or more. However, from the viewpoint of significantly achieving the effects of the present invention, it is preferable that the rubber composition does not contain crosslinking agents and crosslinking accelerators.
[0064] The total content of components (A) and (B) in the rubber composition is not particularly limited, but is, for example, 30 to 70 mass%, preferably 40 to 68 mass%, and more preferably 45 to 65 mass%, relative to the total amount of the rubber composition (100 mass%).
[0065] (silica) As the silica, any silica conventionally known in the art can be used as appropriate. Although not particularly limited, examples thereof include wet silica, dry silica, colloidal silica, etc. These can be used alone or in combination of two or more kinds.
[0066] The surface of the silica may be subjected to a hydrophobic treatment, if necessary. As the hydrophobic treated silica, dimethylsilyl-treated silica and trimethylsilyl-treated silica, which are surface-treated with dimethylsilane or trimethylsilane, are preferred.
[0067] The BET specific surface area of the silica is not particularly limited, but is, for example, 350 m 2 / g or less is preferable, and 80 to 320m 2 / g, 100-300m 2 / g. The BET specific surface area of silica can be measured, for example, by degassing a sample at 200°C for 15 minutes and then using a mixed gas (N2: 70%, He: 30%) as the adsorption gas with a BET specific surface area measuring device (Microdata Corporation, 4232-II).
[0068] The DBA adsorption amount of silica is not particularly limited, but is preferably 10 to 350 mmol / kg, and more preferably 20 to 300 mmol / kg. The DBA adsorption amount can be measured from the amount of dibutylamine (DBA) adsorbed to unreacted silanol groups on the silica surface.
[0069] The content of silica is not particularly limited, but is preferably 20 to 80 parts by mass, and more preferably 30 to 60 parts by mass, per 100 parts by mass of the combined total of the components (A) and (B).
[0070] (Carbon Black) Carbon black may be any of those conventionally known in the art. For example, various grades of carbon black such as SAF, ISAF, HAF, MAF, FEF, GPF, SRF, FT, and MT may be used. These may be used alone or in combination of two or more.
[0071] The nitrogen adsorption specific surface area of carbon black is not particularly limited, but is, for example, 10 to 150 m 2 / g is preferable, and 15 to 100m 2 / g, and even more preferably 20 to 76 m 2 / g, particularly preferably 25 to 65m 2 The nitrogen adsorption specific surface area of carbon black can be measured, for example, by degassing a sample at 200° C. for 15 minutes and then using a mixed gas (N2: 70%, He: 30%) as the adsorption gas with a specific surface area measuring device (Microdata Corporation, 4232-II).
[0072] The iodine adsorption amount of carbon black is not particularly limited, but is, for example, preferably 10 to 150 mg / g, more preferably 10 to 75 mg / g, and even more preferably 20 to 65 mg / g. The DBP (dibutyl phthalate) absorption amount of carbon black is preferably 20 to 180 mL / 100 g, and more preferably 20 to 150 mL / 100 g. The iodine adsorption amount of carbon black is a value measured in accordance with JIS K6217-1 (Method A), and the DBP absorption amount of carbon black is a value measured in accordance with JIS K6217-4.
[0073] The content of carbon black is not particularly limited, but is preferably 0.5 to 15 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of the total of the components (A) and (B).
[0074] When silica and carbon black are used in combination, the content ratio of the two (silica:carbon black) is, for example, 98:2 to 70:30, and preferably 97:3 to 80:20.
[0075] (Anti-aging agent) Examples of the antiaging agent include aromatic secondary amine-based antiaging agents, special wax-based antiaging agents, amine-ketone-based antiaging agents, phenol-based antiaging agents, imidazole-based antiaging agents, etc. These may be used alone or in combination of two or more kinds. The content of the antioxidant is not particularly limited, but is, for example, 0.5 to 5 parts by mass, and preferably 1 to 4 parts by mass, per 100 parts by mass of the total of the components (A) and (B).
[0076] (Processing aids) Examples of processing aids include stearic acid, paraffin wax, polyethylene, peptizer, etc. The content of the processing aid is not particularly limited, but is, for example, 0.5 to 5 parts by mass, and preferably 1 to 4.5 parts by mass, per 100 parts by mass of the total of the (A) component and the (B) component.
[0077] (Method for preparing the present viscoelastic body) The present viscoelastic body can be obtained, for example, by kneading the components (A) to (C) and, if necessary, other components, using a kneader, a planetary mixer, a mixing roll, a twin-screw type agitator, or the like.
[0078] As described above, the vibration damper is characterized in that in any 1 μm × 1 μm square area in a scanning transmission electron microscope image of a viscoelastic body taken at 150,000 times magnification, the number of aggregates, each of which is made up of three or more calcium carbonate particles connected together, is in the range of 3 to 15. By controlling the number of aggregates to the range of 3 to 15, excellent damping characteristics can be exhibited.
[0079] The method for controlling the number of the aggregates within the above range is not particularly limited, but examples thereof include a method of adjusting, within a certain range, the temperature conditions when adding calcium carbonate in the material kneading step in preparing the present rubber composition, and a method of adjusting, within a certain range, the number of kneading cycles after adding calcium carbonate.
[0080] Among these methods, a method in which the temperature condition when calcium carbonate is added in the kneading process of the material is adjusted within a certain range is preferred. Specifically, for example, it is preferred to adjust the temperature (temperature of the kneaded product) when calcium carbonate is added within a range of 50 to 110°C in the rotation speed of a kneading device such as a kneader or the temperature control of the kneading machine. For example, a method in which the temperature of a kneaded product containing at least the (A) component and the (B) component is adjusted to a range of 50 to 110°C, and then the (C) calcium carbonate is added to the kneaded product and kneaded is preferred. When the (C) calcium carbonate is added under a temperature condition lower than the above-mentioned temperature range, the number of aggregates tends to be smaller than the range specified in the present invention, and the damping characteristics tend to be insufficient. Conversely, when the (C) calcium carbonate is added under a temperature condition higher than the above-mentioned temperature range, the number of aggregates tends to be larger than the range specified in the present invention, and the damping characteristics tend to be insufficient.
[0081] More specifically, although not limited thereto, in a production method including a first step of kneading at least the (A) component and the (B) component to prepare a first kneaded product, and a second step of adding and kneading calcium carbonate or the like to the first kneaded product to obtain a second kneaded product, the first step is kneading under conditions of 80 to 150°C for 3 to 15 minutes (preferably 100 to 120°C for 7 to 12 minutes), and the second step is adding calcium carbonate (C) to the kneaded product obtained in the first step under conditions of adjusting the temperature to a range of 50 to 110°C, kneading for 2 to 10 minutes (preferably 3 to 8 minutes), and then kneading under conditions of 80 to 150°C for 3 to 15 minutes (preferably 100 to 120°C for 7 to 12 minutes), which is a suitable production method for controlling the number of aggregates within the above range.
[0082] The temperature condition (temperature of the kneaded product) when adding the calcium carbonate can be appropriately adjusted within a range of 50 to 110° C., and may be adjusted, for example, within a range of 60 to 100° C. or 70 to 90° C. By kneading under such low temperature conditions, a mechanical shear force can be effectively applied, and the dispersion form of calcium carbonate can be effectively controlled.
[0083] In addition, a preferred embodiment of the first step may be a first step in which at least the (A) component, the (B) component, and a filler (excluding the (C) component) are kneaded to prepare a first kneaded product. Specifically, the first step may be a first step in which at least the (A) component, the (B) component, and silica are kneaded to prepare a first kneaded product.
[0084] (Vibration damper manufacturing method) In a method for manufacturing a vibration damper, for example, a rubber composition (viscoelastic body) is prepared as described above, and multiple metal plates of a predetermined size are prepared. The rubber composition (viscoelastic body) is layered on the metal plate, and finally, the metal plate is layered to produce a laminate. An adhesive is applied to the lamination surface of the metal plate in advance.
[0085] An example of this vibration damper is shown in Figure 1. In the figure, 1 is the vibration damper, 2 is the viscoelastic body (viscoelastic layer), and 4 and 5 are metal plates (metal layers). The viscoelastic body (viscoelastic layer) is sandwiched between two metal plates 4 and 5 and bonded to the two metal plates 4 and 5 with an adhesive. Fig. 2 is a cross-sectional view (A-A' cross-sectional view in Fig. 1) showing an example of the present vibration damper. Fig. 2 shows a vibration damper in which the viscoelastic body 2 has a single-layer structure. Although not shown, in the present vibration damper, an adhesive (adhesive layer) is applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic layer) and the metal plate 4 (metal layer), and an adhesive (adhesive layer) is also applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic layer) and the metal plate 5 (metal layer). Fig. 3 is a cross-sectional view showing another example of a vibration damper. Fig. 3 shows a vibration damper in which the viscoelastic body 2 has a two-layer structure. Although not shown, in this vibration damper, an adhesive (adhesive layer) is applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic body layer) and the metal plate 4 (metal layer), and an adhesive (adhesive layer) is also applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic body layer) and the metal plate 5 (metal layer).
[0086] Fig. 4 shows an example of installation of the vibration damper 1. In Fig. 4, 1 is the vibration damper, 2 is a viscoelastic body, 4 and 5 are metal plates, 6 is a bolt, 7 and 8 are panels, 10 is a beam, and 11 is a foundation. As shown in the figure, the metal plates 4 and 5 of the vibration damper 1 are attached to the panels 7 and 8 by the bolt 6, respectively. And, the viscoelastic body 2 sandwiched between the metal plates 4 and 5 functions to damp vibration between the beam 10 and the foundation 11.
[0087] The vibration damper of the present invention is not limited to the shapes described above, and can exhibit excellent functions as a vibration damper for civil engineering and architectural use (also called a vibration damper), a vibration damper for home appliances and electronic devices, etc. In particular, it can perform better as a vibration damper (also called a seismic damper) used in large structures such as bridges and buildings, and particularly as a vibration damper for high-rise buildings. EXAMPLES
[0088] Next, examples will be described together with comparative examples, but the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.
[0089] Example 1 The components shown in Table 1 below were mixed in the ratios shown in the same table to prepare the desired rubber compositions. Specifically, the rubber composition was prepared through a first step of kneading the components (A) and (B) to prepare a master batch, and a second step of adding the remaining materials to the master batch and kneading them. The first step was carried out by kneading at 130° C. for 10 minutes using a kneader. The second step was carried out by adjusting the product temperature of the master batch prepared in the first step to 80° C. using a kneader, adding calcium carbonate and kneading for 3 minutes, and then adding the remaining materials and kneading at 130° C. for 10 minutes.
[0090] Example 2 A rubber composition of Example 2 was obtained in the same manner as in Example 1, except that the temperature condition (product temperature of the master batch) during addition of calcium carbonate was changed to 60°C.
[0091] Example 3 A rubber composition of Example 3 was obtained in the same manner as in Example 1, except that the temperature condition (product temperature of the master batch) during addition of calcium carbonate was changed to 100°C.
[0092] Comparative Example 1 A rubber composition of Comparative Example 1 was obtained in the same manner as in Example 1, except that the temperature condition (product temperature of the master batch) during addition of calcium carbonate was changed to 120°C.
[0093] Comparative Example 2 A rubber composition of Comparative Example 2 was obtained in the same manner as in Example 1, except that the temperature condition (product temperature of the master batch) during addition of calcium carbonate was changed to 45°C.
[0094] [Counting the number of aggregates consisting of three or more calcium carbonate particles] A microtome (Leica, EM UC7) was used to prepare a smooth surface of the rubber composition (viscoelastic body) of the examples and comparative examples, and a scanning transmission electron microscope (JEOL, JEM-2800) was used to take scanning transmission electron microscope images of the rubber composition (viscoelastic body) at a magnification of 150,000 times at four positions. The number of aggregates in a 1 μm x 1 μm square area in the obtained image was visually counted. The average number of aggregates counted at the four positions (rounded off to the nearest whole number) was calculated. The results are shown in Table 1. (Image capture conditions) Magnification: 150,000 times Thickness of sample: 80nm Acceleration voltage: 200 kV Probe size: 1nm Image size (pixels): 512 x 512 Observation mode: STEM-DF (dark field image)
[0095] Specifically, first, a scanning transmission electron microscope image is obtained as described above. Next, an element mapping image is obtained using an energy dispersive X-ray spectrometer (JEM-2800 / SDD100GV, manufactured by JEOL Ltd.) attached to the scanning transmission electron microscope, and calcium carbonate in the microscope image is identified by detecting Ca atoms derived from calcium carbonate. Next, the element mapping image is compared with an enlarged image (1 μm×1 μm square area) of the microscope image, and the number of aggregates consisting of three or more calcium carbonate particles connected together is visually counted. The results are shown in Table 1.
[0096] A more detailed explanation will be given using Example 1 as an example. Fig. 7 shows a scanning transmission electron microscope image of Example 1 (magnification: 150,000 times), Fig. 8 shows an element mapping image of Example 1, and Fig. 9 shows an enlarged screen of the scanning transmission electron microscope image (area of 1 μm×1 μm square). The element mapping image of Fig. 7 and the enlarged screen of the scanning transmission electron microscope image of Fig. 9 (area of 1 μm×1 μm square) are visually compared to count the number of aggregates in the scanning transmission electron microscope image. Note that Fig. 9 shows aggregates of three or more calcium carbonate particles linked together with a circle frame, and shows a dispersion form containing seven aggregates of three or more calcium carbonate particles linked together. The aggregates in each example were aggregates in which 3 to 10 calcium carbonate particles were connected together.
[0097] In counting the number of aggregates, it is preferable to select at least four regions of 1 μm × 1 μm square on an image as described above, observe the dispersion form of calcium carbonate particles in each region, count the number of aggregates, and calculate the average number of aggregates in the four regions.
[0098] [Attenuation characteristic test] The damping properties of the rubber composition were evaluated using an apparatus as shown in Fig. 5. That is, a two-component adhesive for rubber was applied to a predetermined portion (adhesion portion of sample 21) of two metal fittings 22 (size 140 mm x 80 mm, thickness 9 mm) that had been subjected to blasting treatment, and then the rubber composition of the example or comparative example was sandwiched between the two metal fittings 22 and dried. This was subjected to heat press molding at 100°C for 10 minutes to prepare a sample 21 (size 70 mm x 80 mm, thickness 5 mm). The apparatus was then vibrated in the direction of the arrow, and the dynamic shear properties were evaluated based on the load-strain loop curve shown in Fig. 6. That is, a vibration simulating a large earthquake (shear strain rate: 200% (200% of the sample thickness), frequency (f): 0.33Hz, measurement temperature: 20℃) was applied to the above device using a vibration exciter (DYNAMIC SERVO, manufactured by Washimiya Seisakusho Co., Ltd.), an input signal oscillator (Synthesized function generator FC320, manufactured by Yokogawa Electric Corporation), and an output signal processor (Portable FFT analyzer CF-3200, manufactured by Ono Sokki Co., Ltd.) and from an analysis of the shear strain value (δ) and load value (Qd) versus the vibration time, the equivalent stiffness (Ke) and equivalent damping coefficient (Ce) were calculated according to the following formulas (1) to (3), and the damping constant (he) was also calculated from these values. In the following formula, ω=2πf, W=Keδ 2 / 2, ΔW denotes the load-strain loop area (absorbed energy). Equivalent stiffness: Ke(N / mm)=Qd / δ …(1) Equivalent damping coefficient: Ce(kN·s / m)=ΔW / πωδ 2 …(2) Attenuation constant: he = ΔW / 4πW …(3)
[0099] The damping constant in each of the Examples and Comparative Examples was calculated as an index value when the damping constant in Comparative Example 1 was set to 1.0 (standard), and was evaluated according to the following standard. The results are shown in Table 1. (Evaluation Criteria) ◎…Attenuation constant (index conversion value) is 1.20 or more ○…Attenuation constant (index conversion value) is 1.05 or more and less than 1.20 ×…Attenuation constant (index conversion value) is less than 1.05
[0100] [Table 1]
[0101] From the results in Table 1, it can be seen that the samples of the examples satisfy the requirements of the present invention and therefore have excellent damping characteristics. Specifically, it can be seen that the samples have excellent damping characteristics because the number of aggregates, each of which is made up of three or more calcium carbonate particles, is in the specific range of 3 to 15.
[0102] In contrast, the results in Table 1 show that the comparative samples do not satisfy the requirements of the present invention and therefore have insufficient damping characteristics. Specifically, Comparative Example 1, which has 20 aggregates each of which is made up of three or more calcium carbonate particles, was inferior in damping characteristics. Also, Comparative Example 2, which has two aggregates each of which is made up of three or more calcium carbonate particles, was inferior in damping characteristics.
[0103] From the above, it can be seen that the requirements of the present invention are met, that is, a vibration damper having as its constituent member a viscoelastic body made of a rubber composition containing the components (A) to (C), and when the number of aggregates, each of which is made up of three or more calcium carbonate particles connected together, contained in any 1 μm × 1 μm square region in a scanning transmission electron microscope image of the viscoelastic body taken at a magnification of 150,000 is in the range of 3 to 15, has excellent damping characteristics. [Industrial Applicability]
[0104] The vibration damper of the present invention can exhibit excellent functions as a vibration damper for civil engineering and architectural use, as a vibration damper for home appliances and electronic devices, etc. In particular, it can exhibit more excellent functions as a vibration damper used in large structures such as bridges and buildings, and particularly as a vibration damper for high-rise buildings. In addition, vibration control devices and seismic isolation devices such as vibration control walls for buildings, vibration control materials and shock absorbing materials for home appliances and electronic devices, and vibration control materials and shock absorbing materials for automobiles, which are equipped with the viscoelastic material that is a component of the vibration damper of the present invention, can also be used as the vibration damper of the present invention. [Explanation of symbols]
[0105] 1 Vibration damper 2 Viscoelastic body 4,5 Metal plate 6 Volts 7,8 Panel 10 beams 11 Foundation
Claims
1. A vibration damper comprising, as a constituent member, a viscoelastic body made of a rubber composition containing the following components (A) to (C), wherein the number of aggregates, each of which is made up of three or more linked calcium carbonate particles and is contained in any 1 μm × 1 μm square region of a scanning transmission electron microscope image of the viscoelastic body taken at a magnification of 150,000, is in the range of 3 to 15: (A) At least one of a styrene-isoprene-styrene copolymer and a styrene-butadiene-styrene copolymer (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber (C) Calcium carbonate
2. 2. The vibration damper according to claim 1, wherein the number of aggregates each including three or more calcium carbonate particles connected together is in the range of 5 to 9.
3. 3. The vibration damper according to claim 1, wherein the content of said calcium carbonate is 15 to 100 parts by mass per 100 parts by mass of the total of said components (A) and (B).
4. 3. The vibration damper according to claim 1, wherein the calcium carbonate particles have a cubic shape.
5. 3. The vibration damper according to claim 1, wherein the calcium carbonate has an average particle size of 10 to 300 nm.
Citation Information
Patent Citations
High attenuation rubber composition for seismic isolation damper and seismic isolation damper obtained by using the same
JP2014227521A
High attenuation rubber composition for vibration control damper and vibration control damper using the same
JP2015183110A